Scaling up circumcision programs in Southern Africa: the potential impact of gender disparities and changes in condom use behaviors on heterosexual HIV transmission. - Andersson, Kyeen M; Owens, Douglas K; Paltiel, A David (AIDS and behavior, 2011)
Circumcision significantly reduces female-to-male transmission of HIV infection, but changes in behavior may influence the overall impact on transmission. We sought to explore these effects, particularly for societies where women have less power to negotiate safe sex. We developed a compartmental epidemic model to simulate the population-level impact of various circumcision programs on heterosexual HIV transmission in Soweto. We incorporated gender-specific negotiation of condom use in sexual partnerships and explored post-circumcision changes in condom use. A 5-year prevention program in which only an additional 10% of uncircumcised males undergo circumcision each year, for example, would prevent 13% of the expected new HIV infections over 20 years. Outcomes were sensitive to potential changes in behavior and differed by gender. For Southern Africa, even modest programs offering circumcision would result in significant benefits. Because decreases in male condom use could diminish these benefits, particularly for women, circumcision programs should emphasize risk-reduction counseling.
Keywords: Adult; Circumcision, Male; Condoms; Disease Transmission, Infectious; Female; Heterosexuality; HIV Infections; Humans; Male; Mathematics; Models, Theoretical; Prevalence; Risk Reduction Behavior; Sex Factors; Sexual Partners; South Africa; Young Adult